2013
DOI: 10.1186/1532-429x-15-9
|View full text |Cite
|
Sign up to set email alerts
|

European cardiovascular magnetic resonance (EuroCMR) registry – multi national results from 57 centers in 15 countries

Abstract: BackgroundThe EuroCMR registry sought to evaluate indications, image quality, safety and impact on patient management of clinical routine CMR in a multi-national European setting. Furthermore, interim analysis of the specific protocols should underscore the prognostic potential of CMR.MethodsMulti-center registry with consecutive enrolment of patients in 57 centers in 15 countries. More than 27000 consecutive patients were enrolled.ResultsThe most important indications were risk stratification in suspected CAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
145
4
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(173 citation statements)
references
References 31 publications
6
145
4
9
Order By: Relevance
“…These results are substantially in line with those of the Euro-CMR (0.5% of studies performed with 3 T machines) and confirm that both the higher scanners' costs and technical challenges (field homogeneity reduction with increased susceptibility artifacts and radiofrequency-induced power deposition) associated with high field systems are still perceived as major drawbacks by most centers limiting their diffusion and utilization in the territory only to few research sites regardless significant recent improvements and potential advantages of 3 T imaging in CMR [5,10,11].…”
Section: Technical Equipment and Acquisition Protocolssupporting
confidence: 80%
See 1 more Smart Citation
“…These results are substantially in line with those of the Euro-CMR (0.5% of studies performed with 3 T machines) and confirm that both the higher scanners' costs and technical challenges (field homogeneity reduction with increased susceptibility artifacts and radiofrequency-induced power deposition) associated with high field systems are still perceived as major drawbacks by most centers limiting their diffusion and utilization in the territory only to few research sites regardless significant recent improvements and potential advantages of 3 T imaging in CMR [5,10,11].…”
Section: Technical Equipment and Acquisition Protocolssupporting
confidence: 80%
“…The only available register is the EuroCMR, which was recently completed with 27,000 patients and was promoted and organized by the European Society of Cardiology Working Group of "Cardiovascular Magnetic Resonance", with obvious predominant involvement of CMR-dedicated cardiological centers [3][4][5] EuroCMR results convincingly showed that the exam has evolved from the status of "a niche modality" [6] with limited number of cases performed by few tertiary/academic referral into a routine imaging modality, homogeneously diffused and representing an extremely valuable diagnostic support to solve common clinical problems [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A new diagnosis was made in 19%, medication was changed or added in 23%, and other actions taken such as surgery, angiography, biopsy, hospital admission, etc in 13%. This impact on clinical decision making is in the same range as prior published results of large registries7 as well as pooled centers8 and single centers 9. The latter study by Abbasi et al9 was specifically targeted at patients with heart failure with reduced ejection fraction.…”
Section: Introductionmentioning
confidence: 70%
“…28,29 The European Cardiovascular Magnetic Resonance registry, with a clinical follow-up of at least 12 months, observed only a trend towards better outcome in HCM patients without LGE. 30 …”
Section: Discussionmentioning
confidence: 99%